PENGARUH BED OCCUPATION RATE, TURN OVER INTERVAL, AVERAGE LENGHT OF STAY DAN BED TURN OVER TERHADAPKINERJA PROFITABILITAS, DENGAN KINERJA PENDAPATAN SEBAGAI VARIABEL INTERVENING (Study Kasus Pada Rumah Sakit Milik Nusamed Healthcare Tahun 2014-2018) - Hermawan, Dadang; Moehaditoyo, Sri Hartutie; Assery, Wardah (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
The purpose of this research is to analyze the effect of bed occupation rate, turn over interval, average lenght of stay, and bed turn over to performance profitability. PLS is used as the research method in this research with three of Nusamed Healthcare’ Hospital as the sample. The result of this research based on the table of Algorithm Boostrapping, Bed Occupation Rate (BOR) (X1) is significally affecting Revenue Performance (Z). Turn Over Interval (TOI) (X2) is significally affecting Revenue Performance (Z). Average Lenght of Stay (AVLOS) (X3) is proven to affect Revenue Performance (Z). Bed Turn Over (BTO (X4) is significally affecting Revenue Performance (Z). Bed Occupation Rate (BOR) (X1) is proven to affect Profitability Performance (Y). Turn Over Interval (TOI) (X2) is not proven to significally affect Profitability Performance (Y). Average Lenght of Stay (AVLOS) (X3) is not proven to significally affect Profitability Performance (Y). Bed Turn Over (BTO) (X4) is not proven to significally affect Profitability Performance (Y). Revenue Performance (Z) is proven to affect Profitability Performance (Y)